Quantitative anomalous powder diffraction analysis of cation disorder in kesterite semiconductors. Issue 3 (September 2016) - Többens, Daniel M.; Gunder, Rene; Gurieva, Galina; Marquardt, Julien; Neldner, Kai; Valle-Rios, Laura E.; Zander, Stefan; Schorr, Susan
Abstract : Kesterite-type compound semiconductors, containing copper and zinc, have photovoltaic properties depending on cation distribution in the crystal structure. Anomalous diffraction allows discrimination of isoelectronic cations, in principle allowing a straightforward determination of site occupation factors from data collected at multiple energies close to the X-ray absorption edges of copper and zinc. However, extremely strong correlation between structural parameters precludes this. We present a recipe based on the direct dependency between refined occupation factors and atomic scattering power, which allows to lift the correlations and to detect issues of individual diffraction patterns or assumptions in the model, thereby allowing for reliable quantitative analysis of the Cu/Zn distribution.